Secretion of parathyroid hormone may be coupled to insulin secretion in humans - Marie Reeberg Sass (Endocrine Connections, 2020)
Objective: Parathyroid hormone (PTH) is a key hormone in regulation of calcium homeostasis and its secretion is regulated by calcium. Secretion of PTH is attenuated during intake of nutrients, but the underlying mechanism(s) are unknown. We hypothesized that insulin acts as an acute regulator of PTH secretion. Methods: Intact PTH was measured in plasma from patients with T1D and matched healthy individuals during 4-h oral glucose tolerance tests (OGTT) and isoglycemic i.v. glucose infusions on 2 separate days. In addition, expression of insulin receptors on surgical specimens of parathyroid glands was assessed by immunochemistry (IHC) and quantitative PCR (qPCR). Results: The inhibition of PTH secretion was more pronounced in healthy individuals compared to patients with T1D during an OGTT (decrementalAUC0–240min: −5256 ± 3954 min × ng/L and −2408 ± 1435 min × ng/L, P = 0.030). Insulin levels correlated significantly and inversely with PTH levels, also after adjusting for levels of several gut hormones and BMI (P = 0.002). Expression of insulin receptors in human parathyroid glands was detected by both IHC and qPCR. Conclusion: Our study suggests that insulin may act as an acute regulator of PTH secretion in humans.